Generalized anxiety disorder and social media addiction relationships: The role of psychological resilience, doomscrolling and cyberchondria severity - Türk Kurtça Tuğba (Psihologija)
The recent increase in social media use has attracted attention towards its interaction with mental health. This study examined the relationships between generalized anxiety disorder (GAD), social media addiction (SMA), psychological resilience, doomscrolling, and cyberchondria severity. A total of 553 adults (76.1% female, M = 23.25, SD = 6.26) participated in this research. The Generalized Anxiety Disorder Scale (GAD-7), The Brief Resilience Scale (BRS), Doomscrolling Scale (DS), The Short-Form Cyberchondria Severity Scale (CSS-12), Bergen Social Media Addiction (BSMA) were used as measurement tools in this study. The data were analysed using structural equation modeling. To test the null hypothesis regarding the direct and indirect relationships, bootstrapping with 10,000 resamples was performed. Findings indicated that GAD was positively associated with SMA while psychological resilience, doomscrolling, and cyberchondria partially explained the association between GAD and SMA. The bootstrapping procedure showed that both the direct and indirect relations between the variables were statistically significant. The findings suggest that doomscrolling, cyberchondria and psychological resilience may serve as mediators between GAD and SMA.